DIAGNOSTICS OF THE ENTERPRISE PROFITABILITY BY NORMATIVE ACCOUNTING REPORTS - Dmitrenko, A. I. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
Purport, goals, aspects and specificity of enterprise’s profitability evaluation are surveyed. The importance of basic national obligatory accounting statements, namely the balance sheet and income statement, is recognized. Actual approaches to profitability estimation, listed in national enactments in the field of taxation, crediting and privatization are analyzed. Absence of typical approach to enterprises’ profitability also as discrepancy to fundamentals of financial analysis and necessity to adopt given formulas to current accounting reports are identified. Quantity, structure of earnings and profitability ratios are declared the core aspects of enterprise’s profitability analysis. Technology of profit structuring and calculation of profitability indexes are elaborated. It is suggested that the earnings before tax should be splitted onto core activity profit, other operational activity profit, financial activity profit and other activity profit. Profitability ratios are divided onto four groups: financial sources profitability indexes, activity yield indexes, production resources’ profitability ratios and product/department profitability indexes.